CRANIOSYNOSTOSIS AS A PUBLIC HEALTH CHALLENGE – CURRENT KNOWLEDGE ON ETIOLOGY, SYNDROMIC FORMS, AND MANAGEMENT STRATEGIES - Piotr Rejman; Piotr Stachura; Bernadetta Wilk; Edyta Witkowska; Katarzyna Pszczoła; Marcin Ciechański; Szymon Cholewiński; Klaudia Wilk; Katarzyna Jurkiewicz; Aleksandra Kasprzyk (International Journal of Innovative Technologies in Social Science, 2025)
Craniosynostosis is a congenital condition defined by the premature fusion of one or more cranial sutures, leading to abnormal skull morphology and, in some cases, impaired brain development. This review explores the phenotypic variations resulting from different suture involvements, examines the etiology distinguishing syndromic from nonsyndromic forms, and presents an overview of the most common craniosynostosis-associated syndromes, along with their clinical manifestations and systemic complications such as hearing loss and respiratory dysfunction. Additionally, the review summarizes contemporary surgical approaches and timing considerations in the management of this condition.The review highlights significant differences in cranial morphology depending on the specific sutures involved, as well as the diverse clinical profiles of syndromic forms associated with FGFR and TWIST mutations. Syndromes such as Muenke, Apert, and Crouzon exhibit characteristic patterns of suture fusion alongside functional impairments including sensorineural hearing loss and obstructive sleep apnea. Surgical strategies vary based on age, severity, and complexity, with endoscopic techniques preferred in early infancy and open reconstruction favored for older patients or complex cases.A comprehensive understanding of the clinical presentation, genetic basis, and systemic associations of craniosynostosis is essential for accurate diagnosis and individualized treatment planning. Early recognition, timely intervention, multidisciplinary care, and the use of age-appropriate surgical techniques are key to optimizing functional and aesthetic outcomes while supporting long-term health and well-being.